2018
DOI: 10.1002/chem.201801902
|View full text |Cite
|
Sign up to set email alerts
|

Spiro‐epoxyglycosides as Activity‐Based Probes for Glycoside Hydrolase Family 99 Endomannosidase/Endomannanase

Abstract: N‐Glycans direct protein function, stability, folding and targeting, and influence immunogenicity. While most glycosidases that process N‐glycans cleave a single sugar residue at a time, enzymes from glycoside hydrolase family 99 are endo‐acting enzymes that cleave within complex N‐glycans. Eukaryotic Golgi endo‐1,2‐α‐mannosidase cleaves glucose‐substituted mannose within immature glucosylated high‐mannose N‐glycans in the secretory pathway. Certain bacteria within the human gut microbiota produce endo‐1,2‐α‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Subsequent ER processing intermediates were also found to enter the Man-6-P pathway. Further processing of these structures was possibly linked to the enzymatic activity of the endo-α1,2-mannosidase described to be able to cut out a mannose linked to glucoses residues from the A-branch of glycans ( Kukushkin et al., 2012 ) ( Schroder et al., 2018 ). Furthermore, the kinetics of phosphorylated glycans indicated that once the P-GlcNAc group added, there was no longer a site-specific effect on the kinetic, because all phosphorylated had the same kinetic behavior ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent ER processing intermediates were also found to enter the Man-6-P pathway. Further processing of these structures was possibly linked to the enzymatic activity of the endo-α1,2-mannosidase described to be able to cut out a mannose linked to glucoses residues from the A-branch of glycans ( Kukushkin et al., 2012 ) ( Schroder et al., 2018 ). Furthermore, the kinetics of phosphorylated glycans indicated that once the P-GlcNAc group added, there was no longer a site-specific effect on the kinetic, because all phosphorylated had the same kinetic behavior ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…An approach for chemically covalent binding probes was published by Schroder et al 147 Glycosidases cleave N-glycans, which are complex oligosaccharides linked to asparagine residues in proteins. Glycoside hydrolase (GH) family 99 endomannodidase/endomannanase cleaves within complex Nglycans.…”
Section: ■ Spirocycles As Covalent Warheadsmentioning
confidence: 99%
“…To overcome these limitations, the attention has shifted to methods that use a covalent interaction between the compound and its target. This covalent interaction is either established by the reaction of an intrinsic electrophilic group in the parent molecule (for example: epoxides [33,34], carbamates [35], Michael acceptors [36]) that can react with a nucleophilic residue in the protein target, or by introduction of a photo-reactive group that crosslinks upon irradiation with UV light (Figure 1b). The first category is comprised of covalent inhibitors and activity-based probes, and the second of photo-affinity probes, as discussed in more detail below (Section 4.3).…”
Section: Design Of Covalent Probes: Activity-and Affinity-based Probesmentioning
confidence: 99%